2002
DOI: 10.1161/01.cir.0000015856.84385.e9
|View full text |Cite
|
Sign up to set email alerts
|

Angiostatin Inhibits Coronary Angiogenesis During Impaired Production of Nitric Oxide

Abstract: Background-The in vivo mechanism by which inhibition of NO synthase impairs ischemia-induced coronary vascular growth is unknown. We hypothesized that production of the growth inhibitor angiostatin increases during decreased NO production, blunting angiogenesis and collateral growth. Methods and Results-Measurements were made in myocardial tissue or interstitial fluid (MIF) from dogs undergoing repetitive coronary occlusions under control conditions or during antagonism of NO synthase (N G -nitro-L-arginine me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
106
0
5

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(119 citation statements)
references
References 44 publications
8
106
0
5
Order By: Relevance
“…14 -17 In addition to the impairment of endothelium-dependent vasodilation, several mechanisms have now been identified whereby reduced eNO bioavailability may contribute to the pathophysiology of heart failure. In particular, inhibition of eNO production reduces myocardial neovascularization, 18 augments myocardial remodeling, 20 and impairs myocardial perfusion 38,39 and efficiency. 40,41 In the present study, we have evaluated the effect of statin treatment and the role of eNOS for myocardial neovascularization after MI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…14 -17 In addition to the impairment of endothelium-dependent vasodilation, several mechanisms have now been identified whereby reduced eNO bioavailability may contribute to the pathophysiology of heart failure. In particular, inhibition of eNO production reduces myocardial neovascularization, 18 augments myocardial remodeling, 20 and impairs myocardial perfusion 38,39 and efficiency. 40,41 In the present study, we have evaluated the effect of statin treatment and the role of eNOS for myocardial neovascularization after MI.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested that inhibition of endothelium-derived NO production impairs myocardial neovascularization, 18 and statins have the potential to exert proangiogenic effects. 7 We therefore studied the effect of Ator treatment on capillary density in the infarct border zone in WT and eNOS Ϫ/Ϫ mice after MI that was assessed in at least 4 representative border-zone HPFs.…”
Section: Role Of Enos For Ator-induced Effects On Myocardial Capillarmentioning
confidence: 99%
See 1 more Smart Citation
“…Collateral artery formation and ischemia are often associated 19 but not necessarily causally linked. 10 It is highly probable that the venous drainage of collateral flow had induced transient ischemia in the lower leg, as visualized by the increased capillary density in the lower leg muscles (see Table 2).…”
Section: Alternative Explanationsmentioning
confidence: 99%
“…In addition, eNOS increases the production of nitric oxide, which can induce angiogenic responses in vivo and is further induced by VEGF expression [46][47][48]. Reduced nitric oxide production is associated with an impaired angiogenic response [49,50].…”
Section: Discussionmentioning
confidence: 99%